The Prevalence of Hyperuricemia as a Predictive Risk Factor for Gout in Tarhuna City, Libya - Wafa Mohmed,; Naeimah Emran,; Faraj Saqar,; Ibtisam Ahmeed,; Duaa Al-Mahdi,; Salsabil Salama,; Shadha Saleh,; Walaa Nour El-Din, (African Journal of Advanced Pure and Applied Sciences, 2025)
his study investigated the prevalence of hyperuricemia as a predictive risk factor for gout in Tarhuna City, Libya, by analyzing serum uric acid levels across different ages and genders. A retrospective analysis of 1,482 individuals (575 males, 906 females) from multiple medical laboratories between January 2023 and January 2024 was conducted. Results showed uric acid levels increased with age, especially among those aged 76–95 years, with males exhibiting significantly higher mean levels (5.84 mg/dL) than females (4.87 mg/dL). The gender difference is attributed to hormonal factors such as estrogen promoting uric acid excretion in females, as well as physiological and lifestyle differences. The "ALzahra" laboratory was the most commonly used facility, likely due to better accessibility or service quality. The study recommends raising public awareness of hyperuricemia risks, particularly for older adults and males, and improving healthcare services for early detection and management.